Analisis Bahasa dan Simbol Pada Iklan Kemasan Sabun Mandi Shinzui - Lady Diana Yusri (Politeknik Negeri Padang, 2013)
This research aims to analyze the languages and symbols in the advertisement of soap packaging Shinzui. The data in this study used Japanese and English. The theory used to analyze the data is E-135(Sawirman, 2008:1). This theory consists of five stages: elaboration, representation, signification, exploration, and transfiguration.This research is done chronologically based on three steps; they are collecting of the data, analyzing of the data, and presenting the result of analysis. In collecting the data used reading method with non-participant observation technique as basic technique and note-taking technique as follow-up technique. In analyzing the data used agih methods and padan methods. In agih methods using direct element dividing technique and In padan methods used and translational methods. The technique that used in padan methods was dividing element technique. In presenting the result of analysis the data informal methods.After doing the analysis, the writer found that in Shinzui packaging soap is made from natural ingredients that will make this product user skin whiter and healthier. Beside that, these products have been clinically tested. A product reflects the culture in the society. There is an assumption that the pretty lady has skin like a Japanese woman. This advertisement is also represents that Japanese in particular has been popular in Indonesia.